Effect of intravenous administration of Ondansetrone on prevention of anesthesia-induced shivering in gynecologic surgeries: a randomized clinical trial - Farnaz Moslemi; Rayhaneh Abri Sardroudi; Sevda Arashazad; Mohadeseh BijanPour; Maryam Sheydaei (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2020)
Introduction: Regarding the safety of Ondansetronecompared to other anti-shivering drugs, its lower side effects and the contradictory results of its use in the prevention of postoperative shivering, this study was performed with aim to evaluate the effect of preoperative intravenous administration of Ondansetroneon prevention of anesthesia-induced shivering in gynecological surgeries. Methods: This randomized clinical trial study was conducted in 2019 with the participation of 100 women in Alzahra Hospital-Tabriz. Patients were randomly divided into two groups. The intervention group received 2 ml (8 mg) of ondansetroneand the control group received 2 ml of normal saline. The shivering intensity in each patient was recorded according to the shiver severity criterion (LAS). Data were analyzed by SPSS software (version 22) and Chi-square test. P <0.05 was considered statistically significant. Results: Comparison of the number of cases with shivering after anesthesia indicated that 6 (12%) of the ondansetronegroup and 21 (42%) of the control group had shivering intensity >3 that two groups had statistically significant difference (p= 0.001) Conclusion: Ondansetrone, as one of the 5-HT3 antagonists, can be effective in preventing shivering after general anesthesia in gynecological surgeries, but it cannot completely inhibit shivering.